A simple one-pot preparation of N-allenyl amides, ureas, carbamates and sulfonamides using a DMSO/tBuOK protocol. Issue 2 (8th January 2015) - Bousfield, Thomas W.; Kimber, Marc C.
Graphical abstract: Abstract: A one-pot transformation of amides, ureas, carbamates and sulfonamides into synthetically useful N -allenyl analogues using a t BuOK/DMSO protocol is reported. The procedure is experimentally simple and robust, and provides N -allenyl analogues, commonly used within the literature, in yields comparable to the benchmark two-step approach.